Historical Contingencies, Issues of Scale, and Flightless Hypotheses: A Response to Hildebrandt et al. Issue 3 (20th July 2010) - Jones, Terry L.; Codding, Brian F.
Abstract : Hildebrandt et al. offer this rather vitriolic challenge to our conclusions on the Diablo Canyon fauna in order to recast the data in favor of their view that major diachronic trends in western North American prehistory are the product of an increase in men's prestige hunting over time. Here we respond, first by discussing our view of the relationship between historical contingencies and behavioral ecological models, second by showing that the patterns they find in a regional faunal dataset result only from inappropriate aggregation of bone counts, third by questioning the potential prestige value of highly vulnerable species, and finally by making the case that standard behavioral ecological models, punctuated by historical contingencies, provide more parsimonious, albeit less fanciful, explanations for patterning in the western North American faunal record. We conclude by suggesting that when practitioners attempt to explain away empirical variability in order to support a favored hypothesis, it might be time to acknowledge that the hypothesis has failed to take flight.